2006
DOI: 10.1177/1078345806296169
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Sexual Risk and Substance Use Behaviors Among Incarcerated Adolescents

Abstract: Incarcerated adolescents report greater sexual risk than do nonincarcerated peers. High-risk sexual behavior is associated with substance use. To determine how much sexual risk is combined with substance use, 167 incarcerated adolescents reported on their sexual risk behavior in the year before incarceration that involved alcohol or marijuana. For each risk behavior, marijuana use was more likely than was alcohol use. Marijuana use was more common for higher risk behaviors than for lower risk behaviors. Period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
(20 reference statements)
1
25
0
Order By: Relevance
“…This relationship held when the behaviors were measured in general or specifically with reference to the last episode of sex (Kingree et al, 2002). A final study found that sexual risk behaviors among a sample of incarcerated youth were more common in the presence of marijuana than alcohol, especially higher risk behaviors (i.e., sex with someone not known well and sex without a condom) (Rosengard et al, 2006). Co-occurring substance use problems and psychiatric illnesses are widespread among incarcerated adolescents (Crowley & Riggs, 1995;Otto-Salaj et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…This relationship held when the behaviors were measured in general or specifically with reference to the last episode of sex (Kingree et al, 2002). A final study found that sexual risk behaviors among a sample of incarcerated youth were more common in the presence of marijuana than alcohol, especially higher risk behaviors (i.e., sex with someone not known well and sex without a condom) (Rosengard et al, 2006). Co-occurring substance use problems and psychiatric illnesses are widespread among incarcerated adolescents (Crowley & Riggs, 1995;Otto-Salaj et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Again, this result is in line with the findings of many previous studies. (29,(33)(34)(35)(36)(37)(38)(39) Alcohol is an intoxicating drug that depresses the central nervous system, impairs functional brain activity and changes thought processes and feelings. (40) Adolescents may be more vulnerable to the effects of alcohol because they have not developed a physical tolerance for alcohol and lack experience in alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who are involved in the juvenile justice system are at a higher risk of sexually transmitted diseases (including HIV/AIDS) and unplanned-pregnancies than are their non delinquent peers (Rosengard, Barnett, Golembeske, & Lebeau-Craven, 2006). According to Conerly, Robillard and Braithwaite (2006), adolescent females placed in detention facilities typically engage in a number of risky behaviors (including drug use/abuse and risky sexual behavior) at very early ages.…”
Section: Literature Reviewmentioning
confidence: 99%